Identification of a naturally-occurring canine model for early detection and intervention research in high grade urothelial carcinoma - Dhawan, Deepika; Ramos-Vara, José A.; Utturkar, Sagar M.; Ruple, Audrey; Tersey, Sarah A.; Nelson, Jennifer B.; Cooper, Bruce R.; Heng, Hock Gan; Ostrander, Elaine A.; Parker, Heidi G.; Hahn, Noah M.; Adams, Larry G.; et al. (Frontiers in Oncology, 2022)
Background: Early detection and intervention research is expected to improve the outcomes for patients with invasive urinary bladder cancer, specifically muscle invasive urothelial carcinoma (InvUC). With limited patients in suitable high-risk study cohorts, identifying relevant animal models for this research is critical. Experimental animal modes, while essential in InvUC research, often fail to adequately represent human cancer, and fail to predict drug responses. The purpose of this study was to define a naturally-occurring canine model for early intervention research by studying dogs with high breed-associated risk for InvUC, e.g. Scottish Terriers (STs). Methods: STs (n=120) ≥ 6 years old with no outward evidence of urinary disease were screened at 6-month intervals for 3 years. Screening included physical exam with digital rectal exam, ultrasonography, and urinalysis with sediment exam. Cystoscopic biopsy was performed in dogs with positive screening tests. The pathological, clinical, and molecular characteristics of the “early” cancer detected by screening were determined. Transcriptomic signatures were compared between the early tumors and published findings in human InvUC, and to more advanced “later” canine tumors from STs who had the typical clinical presentation of hematuria and urinary dysfunction. An early intervention trial of an oral cyclooxygenase inhibitor, deracoxib, was conducted in dogs with cancer detected through screening. Results: Biopsy-confirmed bladder cancer was detected in 32 (27%) of 120 STs including InvUC (n=29, three starting as dysplasia), grade 1 noninvasive cancer (n=2), and carcinoma in situ (n=1). Transcriptomic signatures including druggable targets such as EGFR and the PI3K-AKT-mTOR pathway, were very similar between canine and human InvUC, especially within luminal and basal molecular subtypes. Marked transcriptomic differences were noted between the early and later canine tumors, particularly within luminal subtype tumors. The deracoxib remission rate (42% CR+PR) compared very favorably to that with single-agent cyclooxygenase inhibitors in more advanced canine InvUC (17-25%), supporting the value of early intervention. Conclusions: The study defined a novel naturally-occurring animal model to complement experimental models for early detection and intervention research in InvUC. Research incorporating the canine model is expected to lead to improved outcomes for humans, as well as pet dogs, facing bladder cancer.